Relationship Between Microclimatic Data, Aroma Component Concentrations and Wine Quality Parameters in the Prediction of Sauvignon blanc Wine Quality - Marais, J.; Calitz, F.; Haasbroek, P.D. (South African Journal of Enology and Viticulture, 2017)
Sauvignon blanc grape chemical and wine sensory data, as well as meteorological data (temperature and visible light radiation), collected in three climatically different wine regions in South Africa over three seasons and from two different canopy treatments were statistically analysed. A model for the prediction and/or definition of Sauvignon blanc wine quality was developed. The model utilises above- and within-canopy radiation and can explain 68.8% of the variation in the cultivar-typical vegetative/asparagus /green pepper intensity of Sauvignon blanc wine. Other significant correlations, e.g. between temperature and monoterpene concentrations, were also obtained. Further research is necessary to test and refine this model for application under different environmental conditions.